2020
DOI: 10.2106/jbjs.20.00184
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Achieving the Patient Acceptable Symptom State for the EuroQol-5 Dimension 1 Year After Total Hip Arthroplasty

Abstract: Background: Patient acceptable symptom state (PASS) thresholds for the EuroQol-5 Dimension-3 Level (EQ-5D-3L) questionnaire have been established for patients being evaluated 1 year following total hip arthroplasty (THA) but with varying derivation cohorts and methods. The aim of this study was to (1) generate an EQ-5D PASS threshold 1 year following THA on the basis of an international patient cohort, (2) validate preexisting and newly generated PASS thresholds 1 year following THA using the insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Keurentjes et al 31 reported a similar threshold for OHS in a study that assessed clinical outcomes three years after THA. Since many factors (such as an anchor used, a deviation cohort, and the observation period) affect the PASS threshold, 29,31 simple comparison is difficult even for the same procedure, and comparison between different procedures can be even more difficult. Nevertheless, as we determined thresholds via the long-term follow-up of cases, our results may be used as a guide for evaluating whether long-term PROMs are favourable after PAO in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Keurentjes et al 31 reported a similar threshold for OHS in a study that assessed clinical outcomes three years after THA. Since many factors (such as an anchor used, a deviation cohort, and the observation period) affect the PASS threshold, 29,31 simple comparison is difficult even for the same procedure, and comparison between different procedures can be even more difficult. Nevertheless, as we determined thresholds via the long-term follow-up of cases, our results may be used as a guide for evaluating whether long-term PROMs are favourable after PAO in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The patientacceptable symptom state (PASS) is defined as a value within the range in which patients feel that the condition of their hip joint is good. 28,29 In the present study, a good hip joint condition after TOA was defined by the following two criteria: 'high satisfaction with the hip joint', and 'no or little hip pain'. One way to determine the PASS is to analyze the response to an anchor question using a receiver operating characteristic (ROC) curve.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported MCII for HOOS are inconsistent (20). A recent study validated PASS for EQ-5D in hip arthroplasty patients (21); however, we were not able to find reports on MCII for EQ-5D after THA surgery. These parameters are therefore not included in our analyses.…”
Section: Discussionmentioning
confidence: 66%